2-Methoxyestradiol Alleviates Neuroinflammation and Brain Edema in Early Brain Injury After Subarachnoid Hemorrhage in Rats - Hu, Qiang; Du, Quan; Yu, Wenhua; Dong, Xiaoqiao (Frontiers in Cellular Neuroscience, 2022)
Objective: Numerous studies have shown that neuroinflammation and brain edema play an important role in early brain injury (EBI) after subarachnoid hemorrhage (SAH). 2-Methoxyestradiol (2-ME) has been shown to have anti-inflammatory and anti-angiogenic effects. This study aimed to investigate the effects of 2-ME on neuroinflammation and brain edema after SAH and its underlying mechanism of action. Method: Rats were used to produce an endovascular puncture model of SAH. 2-ME or the control agent was injected intraperitoneally 1 h after SAH induction. At 24 h after surgery, the neurological score, SAH grading, brain water content, and blood–brain barrier (BBB) permeability were examined. The microglial activation level in the rat brain tissue was determined using immunofluorescence staining, whereas the cell apoptosis in the rat brain tissue was assessed using terminal deoxynucleotidyl transferase dUTP nick-end labeling assay, the levels of Interleukin (IL)-1β, IL-6 and tumour necrosis factor (TNF)-α were measured by enzyme linked immunosorbent assay, and the expression levels of ZO-1, occludin, hypoxia-inducible factor-1α (HIF-1α), vascular endothelial growth factor (VEGF), and matrix metallopeptidase (MMP)-9 in the rat brain tissue were determined using western blotting. Results: Twenty-four hours after SAH, brain water content, BBB permeability, microglial activation, and cell apoptosis were significantly increased, whereas neurological function deteriorated significantly in rats. Treatment with 2-ME significantly decreased brain water content, BBB permeability, microglial cell activation, and cell apoptosis and improved neurological dysfunction in rats. Treatment with 2-ME reduced the expression levels of inflammatory factors (IL-1β, IL-6, and TNF-α), which were significantly elevated 24 h after SAH. Treatment with 2-ME alleviated the disruption of tight junction proteins (ZO-1 and occludin), which significantly decreased 24 h after SAH. To further determine the mechanism of this protective effect, we found that 2-ME inhibited the expression of HIF-1α, MMP-9, and VEGF, which was associated with the inflammatory response to EBI and BBB disruption after SAH. Conclusion: 2-ME alleviated neuroinflammation and brain edema as well as improved neurological deficits after SAH in rats. The neuroprotective effect of 2-ME on EBI after SAH in rats may be related to the inhibition of neuroinflammation and brain edema.